(untitled) (Research, Society and Development, 2020)
This work aimed to determine the capacity of endophytic bacteria isolates to promote the growth of black pepper plants. The endophytic bacteria were inoculated in black pepper seedlings by immersion in bacterial suspension in the concentration of 108 CFU mL-1 for five minutes. The plants of the control treatment were immersed in sterile distilled water. Subsequently, the seedlings were planted in pots containing sterile coconut fiber. Plant height, stem diameter, and dry mass were measured to evaluate the promotion of plant growth. Isolates C5.11, C6.2, T2.2, and C1.4 promoted the growth of black pepper plants with an increase in height and dry matter of 26.82, 27.37, 35.55, and 37.99% and 10.13, 3.92, 6.25, and 10.17%, respectively. Isolate C5.11 promoted an increase of 33.66% in the growth rate of stem diameter compared to the control treatment. Isolates C6.2, T2.2, C5.11, and C1.4 promoted the growth of black pepper plants in this study, with an increase in plant height and dry mass compared to the control treatment.